2011
DOI: 10.1210/jc.2011-0615
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Fat Deposition in Subcutaneous Versus Visceral Depots Is Associated with Insulin Sensitivity

Abstract: These data demonstrate that after adjustment for BMI and VAT mass, sc abdominal and thigh fat are protective for insulin resistance, whereas VAT, after adjustment for SAT and BMI, has the opposite effect. Whether causal in nature or a marker of underlying pathology, these results clarify that regional distribution of fat-favoring sc depots is associated with lower risk for insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
278
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 405 publications
(295 citation statements)
references
References 23 publications
10
278
1
6
Order By: Relevance
“…In addition, our analysis pertains to people from a wide range of backgrounds and origins, reflecting that the development of diabetes is not origin specific. Second, although they did not compromise the outcome definition, measurements of waist circumference or specific fat compartments (27,28), circulating insulin and Cpeptide, were not obtained in this study, limiting our ability to more directly assess adiposity and insulin resistance. Finally, the analysis was conducted only in men, thereby limiting the generalization of the results to women.…”
Section: Resultsmentioning
confidence: 93%
“…In addition, our analysis pertains to people from a wide range of backgrounds and origins, reflecting that the development of diabetes is not origin specific. Second, although they did not compromise the outcome definition, measurements of waist circumference or specific fat compartments (27,28), circulating insulin and Cpeptide, were not obtained in this study, limiting our ability to more directly assess adiposity and insulin resistance. Finally, the analysis was conducted only in men, thereby limiting the generalization of the results to women.…”
Section: Resultsmentioning
confidence: 93%
“…As previously reported 37) , the present study demonstrated that there was an increase in EPA could aggravate vascular inflammation, plaque instability, and neovascularization 23) . In general, AVAT has been reported to be a major contributor to metabolic risk 24,25) , whereas SAT has been suggested to play a protective role 26) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not the most interesting tissue, because SAT correlates less strongly with metabolic risks factors than VAT, as has been demonstrated in the Framingham heart study (Fox et al, 2007). In addition, VAT has been shown to correlate with insulin resistance, whereas SAT is protective against insulin resistance, which has been shown by analysis of VAT and SAT in insulin-resistant and insulinsensitive obese subjects (women and men) by adjusting the relation between SAT and insulin for BMI and VAT (McLaughlin et al, 2011). In our study, insulin and HOMA-IR were positively correlated to VAT, but not to SAT, corroborating the literature observations.…”
Section: Correlations With Bfdmentioning
confidence: 96%